FeCo-NC bimetallic single-atom nanozyme and its preparation method and application
By designing FeCo-NC bimetallic single-atom nanoenzyme, the problem of the reduction of existing antioxidant natural enzymes under pathological conditions is solved, and the effect of efficient removal of reactive oxygen species and increasing NAD+ content is achieved, providing protection against cell damage.
Patent Information
- Application Number
- CN202510082221.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Existing antioxidant natural enzymes are sensitive to environmental conditions, have reduced activity under pathological conditions, and cannot effectively deal with diseases caused by excessive reactive oxygen species.
A FeCo-NC bimetallic monoatom nanozyme was designed to prepare Co-ZIF-8 by using zinc nitrate, cobalt nitrate and 2-methylimidazole, and then reacted with ferric chloride to prepare FeCo-NC nanozyme.
FeCo-NC nanoenzymes exhibit efficient catalase and NADH oxidase activities, which can effectively eliminate excess reactive oxygen species, increase NAD+ content, improve oxidative stress-induced damage, and provide cell protection.
Smart Images

Figure CN119500234B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biocatalysts, and in particular to a FeCo-NC bimetallic single-atom nanozyme and a preparation method and application thereof. Background Art
[0002] Reactive oxygen species (ROS) refer to highly chemically active oxidizing substances, such as superoxide anions, hydroxyl radicals, hydrogen peroxide, etc. They are produced during cell metabolism and are normally involved in cell signaling and immune responses. However, when there are too many ROS, they may cause cell damage and trigger a series of diseases, such as cardiovascular disease, neurodegenerative diseases, cancer, chronic inflammatory diseases, etc. Natural enzymes in the human body, such as antioxidant enzymes (such as superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and horseradish peroxidase (HRP)), can keep ROS in a balanced state and limit its damage to normal cells. NADH oxidase (NOX), as an important mitochondrial respiratory chain enzyme, plays an important role in the electron transfer cascade reaction of mitochondrial oxidative phosphorylation (OXPHOS) and TCA bioenergy production, thereby maintaining the normal function of mitochondria.
[0003] However, antioxidant natural enzymes are highly sensitive to environmental conditions and their activities are often reduced under pathological conditions, making them unable to meet clinical needs. This has prompted extensive research on natural enzyme mimics.
[0004] Therefore, designing highly efficient natural enzyme mimics with multiple antioxidant enzyme activities is of great significance for the treatment of physiological diseases related to reactive oxygen species burst. Summary of the invention
[0005] The present application solves at least one of the problems of the related art from the following aspects.
[0006] The first embodiment of the present application provides a method for preparing a FeCo-NC bimetallic single-atom nanozyme, comprising:
[0007] Preparation of Co-ZIF-8 using zinc nitrate, cobalt nitrate, and 2-methylimidazole; and
[0008] The FeCo-NC bimetallic single-atom nanozyme is prepared using the Co-ZIF-8 and ferric chloride.
[0009] Wherein, the molar ratio of the zinc nitrate to the cobalt nitrate is (20-30):1, and the molar ratio of the cobalt nitrate to the ferric chloride is (2-6):1.
[0010] In some embodiments, the molar ratio of the 2-methylimidazole to the zinc nitrate is (2-6):1.
[0011] In some embodiments, the molar ratio of the zinc nitrate to the cobalt nitrate is (23-27):1, and the molar ratio of the cobalt nitrate to the ferric chloride is (3.5-5.5):1.
[0012] In some embodiments, the molar ratio of the 2-methylimidazole to the zinc nitrate is (2.5-5):1.
[0013] In some embodiments, the Fe content in the FeCo-NC bimetallic single-atom nanozyme is 1.8 wt%-2.2wt%, and the Co content is 2.6 wt%-3 wt%.
[0014] In some embodiments, the preparation method further comprises: pyrolyzing the product prepared from the Co-ZIF-8 and ferric chloride in a nitrogen atmosphere to remove Zn.
[0015] In some embodiments, the preparation method further comprises: pyrolyzing the product prepared from the Co-ZIF-8 and ferric chloride in a nitrogen atmosphere at 900-1000° C. for 1-3 hours to remove Zn.
[0016] The second aspect of the present application provides a FeCo-NC bimetallic single-atom nanozyme prepared by the preparation method of any one of the first aspects above.
[0017] The third aspect embodiment of the present application provides the use of the FeCo-NC bimetallic single-atom nanozyme of any embodiment of the second aspect of the present application in the preparation of a medicament for treating a disease selected from the group consisting of: ischemic stroke and traumatic brain injury.
[0018] The fourth aspect of the present application provides a use of the FeCo-NC bimetallic single-atom nanozyme of any embodiment of the second aspect of the present application in preparing a drug for one or more of the following:
[0019] Used to reduce the content of active oxygen;
[0020] Used to increase NAD + content;
[0021] Used to improve oxidative stress-induced damage;
[0022] Used for catalytic decomposition of hydrogen peroxide;
[0023] Used to catalyze the oxidation of NADH.
[0024] Compared with the prior art, the embodiments of the present invention achieve at least the following beneficial effects:
[0025] The FeCo-N / C provided in the embodiments of the present invention exhibits higher simulated CAT activity than many other reported nanozymes, and its simulated NOX activity is better than that of natural NOX.
[0026] The bimetallic single-atom material FeCo-N / C provided in the embodiment of the present invention can simulate the good ability of CAT and NOX to remove active oxygen, catalyze the decomposition of H2O2 to generate H2O and O2, and catalyze the oxidation of NADH to generate NAD. + In vitro experiments showed that FeCo-N / C nanozymes can remove excess ROS and upregulate NAD + , improved the damage induced by oxidative stress, relieved mitochondrial function and morphology, and provided good protection for cells. It has opened up new ideas for the treatment of brain-related diseases based on the dual targets of clearing ROS and relieving mitochondrial function. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0028] Figure 1 (a) is a scanning electron microscope (SEM) image of FeCo-NC prepared in Example 1; Figure 1 (b) is a transmission electron microscope (TEM) image of FeCo-NC prepared in Example 1; Figure 1 (c) High resolution transmission electron microscopy (HR-TEM) image and selected area electron diffraction (SAED) image (inset) of FeCo-NC prepared in Example 1.
[0029] Figure 2 (a) is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image of FeCo-N / C prepared in Example 1; Figure 2 (b) Figure 2 Enlarged view of the red dashed area in (a), where Fe and Co atoms are represented by red circles.
[0030] Figure 3(a) is a schematic diagram of FeCo-N / C simulating catalase (CAT) and nicotinamide adenine dinucleotide (oxidized) oxidase (NOX), and a photograph of each group (control group, FeCo-N / C, Fe-N / C, Co-N / C, N / C) in the simulated catalase (CAT) activity test in 2.1 of the detection example catalyzing H2O2 to produce O2 bubbles; Figure 3 (b) is the kinetic curve of the decomposition of H2O2 catalyzed by each group of materials in Table 1; Figure 3 (c) The curve of dissolved oxygen in each group of reaction systems in Table 1 over time; Figure 3 (d) is the specific activity of FeCo-N / C simulated catalase (CAT) (U mg -1 ); Figure 3 (e) and Figure 3 (f) is the Michaelis-Menten kinetic measurement results of FeCo-N / C and H2O2.
[0031] Figure 4 (a) is the UV-visible spectrum of each group of Fe-containing diatomic materials in Table 2 when catalyzing the oxidation of nicotinamide adenine dinucleotide (oxidized form) (NADH) for 5 minutes; Figure 4 (b) is the UV-visible spectra of some groups (control group, FeCo-N / C, Fe- N / C, Co-N / C, N / C) in Table 2 when nicotinamide adenine dinucleotide (oxidized form) (NADH) was oxidized for 5 min; Figure 4 (c) is the curve of the absorbance change at 340 nm of some groups (control group, FeCo-N / C, Fe- N / C, Co-N / C, N / C) catalyzed by nicotinamide adenine dinucleotide (oxidized form) (NADH) over time in Table 2; Figure 4 (d) is the UV-visible spectra of the FeCo-N / C group in Table 2 under different atmospheres; Figure 4 (e) is the activity test of nicotinamide adenine dinucleotide (oxidized form) oxidase (NOX) in the simulation of nicotinamide adenine dinucleotide (NAD + ) of the test results produced; Figure 4 (f) is the UV-visible absorption spectrum of hydrogen peroxide generated during the oxidation of nicotinamide adenine dinucleotide (oxidized form) (NADH) catalyzed by FeCo-N / C using 3,3',5,5'-tetramethylbenzidine (TMB) and horseradish peroxidase (HRP) in the detection of nicotinamide adenine dinucleotide (oxidized form) oxidase (NOX) activity in the detection example 2.2.
[0032] Figure 5 (a) The results of cell viability test of mouse neuronal cells HT22 after treatment with different concentrations of FeCo-N / C; Figure 5(b) The results of cell viability detection after incubation of oxygen-glucose deprivation / reperfusion (OGD / R) model cells with different concentrations of FeCo-N / C.
[0033] Figure 6 (a) is the JC-1 fluorescence ratio membrane potential analysis results of each group in the cell experiment of detection example 2.3; Figure 6 (b) is an electron microscope image of FeCo-N / C uptake by HT22 cells of mouse neurons in the OGD / R + FeCo-N / C group in the cell experiment of Example 2.3, scale bar 5 μm; Figure 6 (c) is a representative image of the mitochondrial structure of mouse neuron HT22 cells in each group in the cell experiment of Example 2.3 observed using transmission electron microscopy, where scale bars: 1 μm, 500 nm; ***P<0.001, ****P<0.0001.
[0034] Figure 7 (a) and Figure 7 (b) is the Michaelis-Menten kinetic measurement result of FeCo-N / C and NADH in the simulated NOX activity in detection example 2.2. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Ischemic stroke (IS) is usually caused by cerebral embolism and is the most common type of stroke, accounting for 5.2% of deaths worldwide. After cerebral ischemia, especially reperfusion injury, the massive production of reactive oxygen species (ROS) leads to the occurrence of inflammatory response, while excessive consumption and even inactivation of endogenous antioxidants will seriously hinder the recovery of neurological function. Effective removal of excess ROS can save nerve cells, thereby achieving effective treatment of IS. In addition, the reduction or permanent loss of cerebral blood flow caused by cerebral vascular occlusion will lead to mitochondrial dysfunction and adenosine triphosphate (ATP) consumption, thereby triggering a series of cascade reactions, including excessive ROS production, excitotoxicity and calcium overload.
[0037] After a lot of experimental design and research, the inventors of this application found that the FeCo-N / C provided in the examples of this application has good ability to simulate catalase (CAT) and NADH oxidase (NOX). The FeCo-N / C provided in the examples of this application shows higher CAT simulation activity than many other reported nanozymes, and the simulated NOX activity is better than natural NOX. In in vitro experiments, FeCo-N / C nanozymes can remove excess ROS and upregulate NAD + , improve oxidative stress-induced damage, relieve mitochondrial function and morphology, inhibit cell apoptosis, and provide good protection for cells. A mouse middle cerebral artery occlusion (MCAO) model was further constructed to explore its therapeutic effect on SI. In vivo studies have shown that FeCo-N / C significantly protected MCAO mice, reduced infarct volume, and had almost no toxic side effects.
[0038] The first embodiment of the present application provides a method for preparing a FeCo-NC bimetallic single-atom nanozyme, comprising:
[0039] Preparation of Co-ZIF-8 using zinc nitrate, cobalt nitrate, and 2-methylimidazole; and
[0040] The FeCo-NC bimetallic single-atom nanozyme is prepared using the Co-ZIF-8 and ferric chloride.
[0041] Wherein, the molar ratio of the zinc nitrate to the cobalt nitrate is (20-30):1 (for example, 21:1, 22:1, 23:1, 24:1, 25:1, 26:1, 27:1, 28:1, 29:1), and the molar ratio of the cobalt nitrate to the ferric chloride is (2-6):1 (for example, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1).
[0042] The FeCo-N / C provided in the examples of the present application exhibits higher simulated CAT activity than many other reported nanozymes, and its simulated NOX activity is better than that of natural NOX.
[0043] In some embodiments, the molar ratio of the 2-methylimidazole to the zinc nitrate is (2-6):1 (e.g., 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1).
[0044] In some embodiments, the molar ratio of the zinc nitrate to the cobalt nitrate is (23-27):1 (e.g., 23.5:1, 24:1, 24.5:1, 25:1, 25.5:1, 26:1, 26.5:1), and the molar ratio of the cobalt nitrate to the ferric chloride is (3.5-5.5):1 (e.g., 4:1, 4.5:1, 5:1).
[0045] In some embodiments, the molar ratio of the 2-methylimidazole to the zinc nitrate is (2.5-5):1 (eg, 3:1, 3.5:1, 4:1, 4.5:1).
[0046] In some embodiments, the Fe content in the FeCo-NC bimetallic single-atom nanozyme is 1.8 wt%-2.2wt% (e.g., 1.85 wt%, 1.9 wt%, 1.95 wt%, 1.98 wt%, 2 wt%, 2.05 wt%, 2.1 wt%, 2.15wt%), and the Co content is 2.6 wt%-3 wt% (e.g., 2.7 wt%, 2.8 wt%, 2.83 wt%, 2.9 wt%).
[0047] In the present embodiment, a FeCo-NC bimetallic single-atom nanozyme is obtained by selecting an appropriate ratio of Fe and Co (Co content is higher than Fe content), which has excellent ability to simulate catalase and NADH oxidase. When the ratio of the Co element is reduced, for example, when the Co content is lower than the Fe content, its CAT enzyme-like and NOX-like activities are significantly reduced.
[0048] In some embodiments, the preparation method further comprises: pyrolyzing the product prepared from the Co-ZIF-8 and ferric chloride in a nitrogen atmosphere to remove Zn.
[0049] In some embodiments, the preparation method further includes: pyrolyzing the product prepared from the Co-ZIF-8 and ferric chloride at 900-1000°C (e.g., 910°C, 920°C, 930°C, 940°C, 950°C, 960°C, 970°C, 980°C, 990°C) in a nitrogen atmosphere for 1-3 hours (e.g., 1.5 hours, 2 hours, 2.5 hours) to remove Zn.
[0050] The second aspect of the present application provides a FeCo-NC bimetallic single-atom nanozyme prepared by the preparation method of any one of the first aspects above.
[0051] The third aspect of the present application provides a use of the FeCo-NC bimetallic single-atom nanozyme of any embodiment of the second aspect of the present application in the preparation of a medicament for treating a disease selected from the group consisting of: ischemic stroke and traumatic brain injury.
[0052] The fourth aspect of the present application provides a use of the FeCo-NC bimetallic single-atom nanozyme of any embodiment of the second aspect of the present application in preparing a drug for one or more of the following:
[0053] Used to reduce the content of active oxygen;
[0054] Used to increase NAD + content;
[0055] Used to improve oxidative stress-induced damage;
[0056] Used for catalytic decomposition of hydrogen peroxide;
[0057] Used to catalyze the oxidation of NADH.
[0058] For the sake of brevity, the disclosures of publications, including patents and patent applications, cited in this specification are incorporated herein by reference in their entireties.
[0059] Most chemical names were generated using IUPAC nomenclature. Some chemical names were generated using different nomenclature or alternative names or commercial names known in the art. In the event of a conflict between a name and structure, the structure controls.
[0060] Definitions and General Terms
[0061] Reference will now be made in detail to certain embodiments of the present invention, examples of the present invention are illustrated in the appended structures and chemical formulas. The present invention is intended to cover all alternatives, modifications and equivalents that may be included within the scope of the present invention as defined by the claims. Those skilled in the art will recognize that many methods and materials similar or comparable to the methods and materials described herein may be used in the practice of the present invention. The present invention is by no means limited to the methods and materials described herein. In the case where one or more of the incorporated documents, patents and similar materials are different or contradictory from the present application (including but not limited to defined terms, term usage, described technology, etc.), the present application shall prevail.
[0062] It should also be understood that certain features of the present invention described in the context of different embodiments for clarity may also be provided in combination in a single embodiment. On the contrary, for brevity, the various features of the present invention described in the context of a single embodiment may also be provided separately or in any suitable sub-combination.
[0063] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. All patents and publications mentioned herein are incorporated herein by reference in their entirety.
[0064] As used herein, unless otherwise indicated, the following definitions shall apply. For purposes of the present invention, chemical elements are identified according to the Periodic Table of the Elements, CAS version, and Handbook of Chemistry and Physics, 75th edition (1994). In addition, the general principles of organic chemistry are described in "Organic Chemistry", Thomas Sorrell, University Science Books, Sausalito: 1999 and "March's Advanced Organic Chemistry" by Michael B. Smith and Jerry March, John Wiley & Sons, New York: 2007, the entire contents of which are incorporated herein by reference.
[0065] As used above, and throughout this disclosure, unless otherwise indicated, the following terms are understood to have the following meanings. In the absence of a definition, conventional definitions known to those skilled in the art prevail. If the definition provided herein conflicts or differs from the definition provided in any cited publication, the definition provided herein prevails.
[0066] As used herein, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.
[0067] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0068] In order to provide a more concise description, some quantitative expressions given herein are not limited by the term "about". It should be understood that, whether or not the term "about" is explicitly used, each quantity given herein means the actual given value, and also means the approximate value of such a given value that can be reasonably inferred based on the ordinary technology in the art, including equivalent values and approximate values caused by the experimental and / or measurement conditions of such a given value. Whenever the yield is given in percentage, such a yield refers to the mass of the same entity relative to the maximum amount of the entity that may be obtained under specific stoichiometric conditions. Unless otherwise indicated, the concentration given in percentage refers to the mass ratio.
[0069] As used herein, numerical ranges are intended to include continuous integers. For example, a range expressed as "0 to 4" or "0-4" includes 0, 1, 2, 3, and 4, and a range expressed as "10-20%" includes 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, and 20%. Similarly, numerical ranges are also intended to include continuous fractional integers. For example, a range expressed as "1-2%" will include 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, and 2.0%.
[0070] Example
[0071] 1.1 Preparation of FeCo-N / C materials
[0072] 0.588 g Zn(NO3)2·6H2O (1.98 mmol) and 0.023 g Co(NO3)2·6H2O (0.079 mmol) were dissolved in 15 mL methanol and stirred for 20 minutes to obtain the first solution. 0.616 g 2-methylimidazole (7.5 mmol) was dissolved in 15 mL methanol and ultrasonicated for 20 minutes to obtain the second solution.
[0073] The first solution and the second solution were mixed and stirred for 24 h, washed with methanol, and dried under vacuum at 60 °C overnight to obtain 300 mg Co-ZIF-8.
[0074] 300 mg Co-ZIF-8 was dissolved in 25 mL n-hexane and ultrasonicated for 1 h. 100 μL 50 mg / mL FeCl3·6H2O (0.0185 mmol) was added, and the mixture was centrifuged and dried overnight at 60 °C in vacuum. The obtained product was calcined at 900 °C for 2 h under nitrogen atmosphere to obtain FeCo-N / C.
[0075] According to inductively coupled plasma optical emission spectroscopy (ICP-OES) detection, the obtained FeCo-N / C material contains 1.98wt% of Fe element and 2.83wt% of Co element.
[0076] Figure 1 (a) is the SEM of FeCo-NC prepared in Example 1; Figure 1 (b) TEM image of FeCo-NC prepared in Example 1; Figure 1 (c) HR-TEM image and SAED image (inset) of FeCo-NC prepared in Example 1.
[0077] Figure 2(a) is the HAADF-STEM image of FeCo-N / C prepared in Example 1; Figure 2 (b) Figure 2 Enlarged view of the red dashed area in (a), where Fe and Co atoms are represented by red circles.
[0078] according to Figure 1 and Figure 2 It can be seen that the FeCo-NC material prepared in Example 1 is a non-crystalline structure without nanoparticles, and is in atomic form, with N, Fe and Co elements successfully doped.
[0079] 1.2 Preparation of reference sample Fe-N / C material
[0080] At room temperature, 0.588 g of Zn(NO3)2·6H2O (1.98 mmol), 100 μL of 50 mg / mL FeCl3·6H2O (0.0185 mmol) mixed metal salts and 0.616 g of 2-methylimidazole (7.5 mmol) were dissolved in 150 mL of methanol solution. The two solutions were quickly mixed and allowed to stand at 60 ºC for 12 hours and then stirred for 12 h. After washing with methanol, the mixture was dried in vacuum to obtain 0.1 g of Fe-ZIF-8. Fe-ZIF-8 was heated at 2 ºC min -1 The reaction mixture was heated to 1000 °C at a heating rate of 1.5 ℃ and kept for 1 h under argon atmosphere. Finally, Fe-N / C catalyst was obtained.
[0081] 1.3 Preparation of reference sample Co-N / C material
[0082] 0.588 g Zn(NO3)2·6H2O (1.98 mmol) and 0.023 g Co(NO3)2·6H2O (0.079 mmol) were dissolved in 15 mL of methanol and stirred for 20 minutes. 0.616 g 2-methylimidazole (7.5 mmol) was dissolved in 15 mL of methanol and ultrasonically treated for 20 minutes. The two solutions were then mixed and stirred for 24 hours, washed with methanol, and dried at 60 °C in vacuum overnight to obtain Co-ZIF-8. The above product was calcined at 900 °C for 2 hours under nitrogen atmosphere to obtain Co-N / C.
[0083] 1.4 Preparation of reference sample N / C material
[0084] Dissolve 0.588 g Zn(NO3)2·6H2O (1.98 mmol) in 15 mL methanol and stir for 20 minutes. Dissolve 0.616 g 2-methylimidazole (7.5 mmol) in 15 mL methanol and treat with ultrasound for 20 minutes. Then mix the two solutions, stir continuously for 24 h, wash with methanol, and dry at 60 °C in vacuum overnight to obtain ZIF-8. Dissolve 300 mg ZIF-8 in 25 mL n-hexane and treat with ultrasound for 1 h. The above product was calcined at 900 °C for 2 h under nitrogen atmosphere to obtain N / C.
[0085] 1.5 Preparation of reference sample FeCu-N / C material
[0086] At room temperature, 0.1 g of Fe-ZIF-8 prepared in step 1.2 was dispersed in 12 mL of n-hexane and ultrasonicated for 1 h. Then 0.94 mL of 25 mg mL -1 Cu(NO3)2·6H2O (0.079mmol) methanol solution was added dropwise, stirred for 1 h after ultrasonication, washed with methanol and dried in vacuum to obtain FeCu-ZIF-8. -1 The reaction mixture was heated to 1000 °C at a heating rate of 1.5 ℃ and kept for 1 h under argon atmosphere. Finally, the FeCu-N / C catalyst was obtained.
[0087] 1.6 Preparation of reference sample FeMn-N / C material
[0088] Similarly, FeMn-ZIF-8 was prepared using 0.1 g of the Fe-ZIF-8 prepared in step 1.2 and 0.079 mmol Mn(NO3)2·6H2O to obtain FeMn-N / C material.
[0089] 1.7 Preparation of reference sample FeNi-N / C material
[0090] Similarly, FeNi-ZIF-8 was prepared using 0.1 g of the Fe-ZIF-8 prepared in step 1.2 and 0.079 mmol Ni(NO3)2·6H2O to obtain FeNi-N / C material.
[0091] 1.8 Preparation of reference sample FeMo-N / C material
[0092] Similarly, FeMo-ZIF-8 was prepared using 0.1 g of the Fe-ZIF-8 prepared in step 1.2 and 0.079 mmol Mo(NO3)2·6H2O to obtain FeMo-N / C material.
[0093] Test example
[0094] 2.1 The simulated CAT activities of FeCo-N / C and reference samples (Fe-N / C, Co-N / C and N / C, etc.) were determined respectively.
[0095] Table 1
[0096]
[0097] The samples shown in Table 1 above were used to catalyze the decomposition of H2O2 to generate O2 bubbles, among which FeCo-N / C showed significant simulated CAT activity (see Figure 3 (a)-(f)). The simulated CAT activity of FeCo-N / C and its comparative materials was analyzed by monitoring the UV-visible spectrum of the reaction system containing hydrogen peroxide at 240 nm ( Figure 3 (b)). As time goes by, the absorbance of the reaction system containing hydrogen peroxide decreases significantly, indicating that the hydrogen peroxide has been decomposed. At the same time, the dissolved oxygen content in the reaction system was measured. Figure 3 (c) Compared with the control group and the N / C group, the other groups all produced oxygen, and Figure 3 Comparison of the curves in (c) shows that the catalytic activity of FeCo-N / C is significantly better than that of other reference samples.
[0098] In addition, the catalytic activity of FeCo-N / C for H2O2 decomposition was evaluated. The specific activity (U mg -1 )( Figure 3 (d)), the specific activity of FeCo-N / C CAT simulation was 76.9 U mg -1 .
[0099] In addition, the Michaelis-Menten kinetic curve was obtained using the initial rate (within 100 s) and concentration of hydrogen peroxide ( Figure 3 (e)-(f)). According to the Michaelis-Menten equation, with H2O2 as substrate, the Km of FeCo-N / C was 4.64 mM and the vmax was 3.31×10 -2 mM S -1 , whose affinity is 11.2 times that of natural catalase ( Advanced Materials. 2022, 34(439): 05324. ), indicating that the FeCo-N / C material prepared in Example 1 of the present invention has a higher affinity for H2O2.
[0100] 2.2 Simulated NOX activity
[0101] Table 2
[0102]
[0103] The groups of samples shown in Table 2 above were used to catalyze NADH oxidation.
[0104] In order to explore the NOX simulation activity of FeCo-N / C, NADH was mixed with FeCo-N / C or reference materials (see Table 2 above), and the absorbance at 340 nm was measured after incubation for 5 min. The absorbance was compared with that of NADH of the same concentration without adding materials (using an equal amount of PBS buffer instead), indicating that FeCo-N / C had a better catalytic effect ( Figure 4 (a)-4(c)). When catalyzing NADH oxidation, after incubation for 5 min, whether compared with FeCu-N / C, FeMn-N / C, FeNi-N / C and FeMo-N / C ( Figure 4 (a)), or compared with Fe-N / C, Co-N / C and N / C ( Figure 4 (b)), FeCo-N / C has the best simulated NOX activity. Figure 4 (c) shows the absorbance variation curves of FeCo-N / C group, Fe-N / C group, Co-N / C group and N / C group over time. Figure 4 (c) It can be seen that the absorbance of the FeCo-N / C group decreases fastest and approaches 0 in 10 min.
[0105] In order to verify whether FeCo-N / C plays a role as a catalyst in catalyzing NADH, experiments were conducted in different atmospheres. The oxidation rate of NADH in O2 saturated solution was more significant, while the oxidation rate in Ar saturated solution was slower ( Figure 4 (d)), indicating that oxygen is essential in the catalytic process.
[0106] Based on the catalytic reaction of natural NOX, NADH can be oxidized to the biologically active cofactor NAD + , or inactive cofactor dimer (NAD)2 ( Chemical Engineering Journal. 2022, 440(5): 135810. ). In order to verify the catalytic activity of FeCo-N / C on NADH and NAD + In order to generate NAD, glucose and glucose dehydrogenase (GDH) were added to the reaction system of FeCo-N / C group to convert NAD + Reduction to NADH ( Nano Research. 2023, 16(65): 6615. ). After incubation for 1000 s, glucose and GDH were added, and the absorbance was continuously monitored at 340 nm. It was found that NADH recovered by about 90%, indicating that NAD + is the main oxidation product ( Figure 4(e)). After NADH and FeCo-N / C were mixed and reacted, FeCo-N / C was removed by filtration and centrifugation (to prevent FeCo-N / C from affecting the experimental results) to obtain a supernatant. Then, 25 μg / mL horseradish peroxidase (HRP) and 3 mM 3,3,5,5-tetramethylbenzidine (TMB) were added to the supernatant as the experimental group (TMB+HRP+ reaction solution supernatant). The characteristic absorption peak of oxidized TMB at 652 nm was not detected ( Figure 4 (f)). H2O2 was added to the supernatant as a control group (TMB+HRP+ H2O2), where an obvious absorption peak was detected ( Figure 4 (f)). Therefore, it is speculated that no H2O2 is produced during the catalytic oxidation of NADH by FeCo-N / C, or the excellent CAT-like activity of the catalyst rapidly decomposes the produced H2O2, resulting in the inability to detect hydrogen peroxide in the final system. In addition, according to the Michaelis-Menten equation, with NADH as the substrate, the Km value of FeCo-N / C catalyzing the oxidation of NADH is 51.4 μM ( Figure 7 ), which is much lower than NOX (0.35 mM). Moreover, FeCo-N / C material still has good catalytic activity under non-physiological pH and temperature conditions, and the activity can be maintained above 90%.
[0107] 2.3 Cell experiments
[0108] 2.1 and 2.2 above have demonstrated that FeCo-N / C has the potential to remove H2O2 and NAD + Furthermore, the examples of the present application verified the ability of FeCo-N / C to remove ROS, relieve mitochondrial function and inhibit cell apoptosis through in vitro cell experiments.
[0109] To ensure the safety of FeCo-N / C, we first used CCK-8 to detect the cytotoxicity of FeCo-N / C to HT22 cells after 24 h of incubation. The CCK-8 results showed that FeCo-N / C had no significant effect on HT22 cells at a concentration below 50 μg mL -1 When FeCo-N / C was used, there was almost no obvious cytotoxicity ( Figure 5 (a)), which indicates that the nanomaterial is safe in subsequent experiments.
[0110] OGD / R (Oxygen and Glucose Deprivation / Recovery) has been widely used in stroke research as an in vitro model to simulate SI. When oxygen and glucose deprivation is restored, ROS burst will occur, eventually leading to cell damage and death. The method for constructing the OGD / R model in the embodiments of this application refers to Expression changes of the notchsignaling pathway of PC12 cells after oxygen glucose deprivation, DOI:10.1016 / j.ijbiomac.2018.07.039.
[0111] A control group, an OGD / R group, and an OGD / R + FeCo-N / C (or Fe-N / C, Co-N / C, N / C) group were set up. After 24 hours of incubation, the cell viability of each group was detected by CCK-8 method. The results are shown in Figure 5 (b) As shown. It can be seen that OGD / R damage significantly inhibits the proliferation of HT22 cells ( Figure 5 (b) ), while different concentrations of FeCo-N / C (6.25, 12.5 and 25 μg mL -1 ) restored the viability of HT22 cells and protected them from OGD / R-induced oxidative damage ( Figure 5 (b)), indicating that FeCo-N / C has a protective effect against oxidative stress damage, which is superior to other comparison materials.
[0112] Figure 6 The control group, OGD / R group, and OGD / R + FeCo-N / C group (FeCo-N / C concentration was 12.5 μg mL -1 ) test results, where Figure 6 (a) JC-1 fluorescence ratio membrane potential analysis of each group; Figure 6 (b) is the electron microscope image of FeCo-N / C uptake by HT22 cells of mouse neurons in the OGD / R + FeCo-N / C group, with a scale bar of 5 μm, indicating that the cells successfully absorbed the FeCo-N / C material; Figure 6 (c) is a representative image of the mitochondrial structure of mouse neuron HT22 cells observed by transmission electron microscopy in each group of the cell experiment in detection example 2.3, where the scale bar is 1 μm, 500 nm; ***P<0.001, ****P<0.0001. Figure 6 (c) It can be seen that FeCo-N / C can restore HT22 cells damaged by OGD / R.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A FeCo-NC bimetallic single-atom nanozyme is prepared for increasing NAD + The use of a drug for containing or catalyzing the oxidation of NADH, characterized in that: The preparation method of the FeCo-NC bimetallic single-atom nanozyme comprises: Preparation of Co-ZIF-8 using zinc nitrate, cobalt nitrate, and 2-methylimidazole; and The FeCo-NC bimetallic single-atom nanozyme is prepared using the Co-ZIF-8 and ferric chloride. Among them, the molar ratio of the zinc nitrate to the cobalt nitrate is (20-30):1, the molar ratio of the cobalt nitrate to the ferric chloride is (2-6):1, and the content of Fe in the FeCo-NC bimetallic single-atom nanozyme is 1.8wt%-2.2wt%, and the content of Co is 2.6wt%-3wt%.
2. The use according to claim 1, characterized in that The molar ratio of the 2-methylimidazole to the zinc nitrate is (2-6):
1.
3. The use according to claim 1, characterized in that The molar ratio of the zinc nitrate to the cobalt nitrate is (23-27):1, and the molar ratio of the cobalt nitrate to the ferric chloride is (3.5-5.5):
1.
4. The use according to claim 2, characterized in that: The molar ratio of the 2-methylimidazole to the zinc nitrate is (2.5-5):
1.
5. The use according to claim 1, characterized in that: The method for preparing the FeCo-NC bimetallic single-atom nanozyme further includes: pyrolyzing the product prepared from the Co-ZIF-8 and ferric chloride in a nitrogen atmosphere to remove Zn.
6. The use according to claim 5, characterized in that The preparation method of the FeCo-NC bimetallic single-atom nanozyme further includes: pyrolyzing the product prepared from the Co-ZIF-8 and ferric chloride in a nitrogen atmosphere at 900-1000° C. for 1-3 hours to remove Zn.
Citation Information
Patent Citations
High-dispersion Co-based bimetallic catalyst based on ZIFs and preparation method thereof
CN112973758A